Pengaruh Transfer Pemerintah Pusat terhadap Perilaku Fiskal Pemerintah Daerah di Provinsi Kalimantan Timur - Murniasih, Erny; Mulyadi, M. Syarif (UI Scholars Hub, 2011)
Over the last decade of Indonesia's fiscal decentralization era, the amount of intergovernmental fiscal transfers has increased substantially. The increase of intergovernmental fiscal transfers is expected to reduce the burden of local economy without sacrificing the quality of public service. This study aims to investigate whether the block grant transfer affect the spending behavior of local government. Using Pool Least Square method and taking East Kalimantan Province as case study, this study found the existence of flypaper effect. This finding emphasize the view of any increase in block grant of transfer will only induce higher spending. Therefore, in order to achieve the independency of local government as the objective of decentralization, some efforts should be taken to minimize the impact of flypaper effect.